Strategy to Increase Arabic Vocabulary Size among Secondary School Students in Setiu District, Terengganu - Ahmad Sabri, Abdul Salam; Suhaimi, Muhammad Faris; Wan Ahmed, Wan Aswadi (SIBAWAYH Arabic Language and Education, 2023)
Learning strategies are essential for effective language learning and acquisition, helping students learn new words and strengthen their understanding and application in real-life contexts. Therefore, this study aims to explore Arabic vocabulary learning strategies among students in Setiu district, Terengganu, Malaysia by using qualitative methods. Ten respondents who were selected using purposive sampling techniques participated in this study. All respondents have met the criteria set by the researcher. The results obtained were analyzed using ATLAS.ti software by using a thematic analysis approach. The findings show six main strategies to improve Arabic vocabulary, namely implementing a structured Arabic language program, using correct memorization techniques, combining vocabulary games, creating an Arabic corner, using appropriate teaching aids, and reviewing regularly.